PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA MELALUI VARIABEL MOTIVASI KARYAWAN GRAN MELIA HOTEL JAKARTA - Putri Andrayani; Bonifasius M.H Nainggolan (LPPM Universitas Asa Indonesia, 2017)
Purpose- To find out the influence of leadership and work performance through motivational variables both partially and simultaneously at the Gran Melia Jakarta hotel. Design/methodology/approach- to find out the influence of leadership and work performance through motivational variables both partially and simultaneously at the Gran Melia Jakarta hotel. Findings- From this analysis we can see that leadership has a significant influence on performance through motivation partially or simultaneously. Meanwhile, work discipline does not have a significant effect on performance through motivational variables.